Engineering Electromagnetics - Hayt, W H; Buck, J A (New Delhi : Tata McGrow Hill, 2006)
Engineering
Keywords: Engineering; Electromagnetics; Engineers; Energy and Potential; Current and Conductors; Dielectrics and Capacitance; Magnetic Field; Magnetic Forces; Transmission Lines; Waves and Radiation